Dinamika Id, Ego, dan Superego Kepribadian Tokoh Utama Dalam Novel Proyek Maut Karya Eddie Sindunata - Nuryana, Muhamad Rian; Rohanda , Rohanda (Green Publisher Indonesia, 2025)
This study aims to uncover the dynamics of the personality structure of the main character in the novel Project of Death by Eddie Sindunata using Sigmund Freud's psychoanalytic approach, which includes three main components: id, ego, and superego. The main character in the novel, Hardi Setiawan, is analyzed to identify inner conflicts as well as ego defense mechanisms that arise in response to psychological pressure. The method used in this study is qualitative descriptive, with data collection techniques through in-depth reading of texts, dialogue recording, and narratives that reflect the psychological aspects of the characters. The results of the study show that the dynamics of id, ego, and superego in Hardi are manifested through spontaneous impulses (id), logical considerations (ego), as well as moral awareness and professional responsibility (superego). Conflicts between these three personality structures create complex internal tensions, which are resolved through ego defense mechanisms such as rationalization and sublimation. These findings confirm the relevance of Freud's theory in studying fictional characters, as well as enriching the understanding of literary works as a mirror of human psychological conditions. This research is expected to contribute to the development of the study of literary psychology in Indonesia, especially in interpreting the complexity of character personalities through a psychoanalytic approach..